Capital intensity and investment shocks: Implications for stock returns - Knesl, J (2017)
I show that a firm’s capital intensity affects the asset pricing implications of investment-specific technology shocks measured by a popular measure, the IMC porfolio. Capital-intensive stocks sorted by the exposure to this measure generate a highly significant average return premium of up to 5% annually. A similar return premium is present in the sub-sample of capital-intensive firms but absent among labor-intensive firms, while the exposures to the IMC portfolio are similar in both sub-samples. This finding is a puzzle since similar exposures to this measure of investment shock generate a very different return premium for capital-intensive and labor-intensive firms. To explain this puzzle, I extend prior models of the investment-specific technology shocks by a novel dimension; firm’s capital intensity. The model can rationalize these empirical findings.